Effect of Education on Women’s Autonomy in Financial Household Decision-making in Afghanistan (American Journal of Youth and Women Empowerment, 2022)
The research study explores the main factors shaping women’s autonomy in financial household decision-making in Afghanistan. This study uses data from the Central Statistics Organization of Afghanistan for 2014. The aim of the research is to conduct an empirical analysis of the main determinants of women’s autonomy in financial household decision-making covering 34 provinces of Afghanistan. The methodology employed in investigating the effect of each factor is the Multinomial Logistic estimation technique. In addition, women’s autonomy relating to expenditure on food, purchasing, and visiting family has been studied. Findings of the study reveal that education has a significant negative effect on women’s participation in financial household decision-making in Afghanistan. In most cases, agricultural employment tends to empower women in terms of financial household decision-making and their autonomy in terms of visiting family, purchasing food, and expenditure. However, other types of employment, including business employment, significantly decrease women’s autonomy in household decision-making. Also, provinces that aren't safe make it much harder for women to make their own financial decisions for their households. In terms of education, it cannot be concluded that education does not play any role in empowering women. Indeed, it plays a vital role in the overall development of the country. Awareness building program, security and health care services from government might be suggested for the bright future of the women in Afghanistan.